Sclerosing encapsulating peritonitis presenting with paroxysmal abdominal pain and strangulated mechanical bowel obstruction: A case report - Tang, Hua (Medicine (Baltimore), 2021)
RATIONALE: Sclerosing encapsulated peritonitis (SEP) is a rare chronic peritoneal inflammation with unknown etiology, and is also known as abdominal cocoon. This occurs when the intestinal annulus is enveloped in the peritoneal cavity, resulting in intestinal obstruction. Its preoperative diagnosis and treatment strategy remains a challenge. PATIENT CONCERNS: The study reports a 53-year-old male, who presented with a 4-day history of paroxysmal abdominal pain, without the adverse reaction of nausea, vomiting, or diarrhea. DIAGNOSIS: The accurate diagnosis of SEP was made after the emergency diagnostic laparoscopy. INTERVENTIONS: The laparoscopic exploration revealed that the small intestine was wrapped by a layer of peritoneum. Then, the abdominal fibrous membrane was removed surgically, and adhesiolysis were performed. The patient recovered well, and gradually recovered by the 10(th) post-operative day. OUTCOMES: The patient was discharged uneventfully after 10 days, and the patient recovered well. After the 12-month follow-up, no symptoms of recurrence or complications were observed. LESSONS: The preoperative diagnosis of SEP remains difficult, and the onset of SEP has exhibited a younger trend. The diagnosis of SEP should remain on the list of differential diagnosis for paroxysmal abdominal pain. single-photon emission computed tomography/computed tomography and laparoscopic exploration have been proven to be helpful for establishing the diagnosis. In the early stage of intestinal obstruction caused by SEP, surgical intervention was immediately carried out in emergency department, and the patient recovered well after the operation. The present study also presents a review of the literature for other cases of SEP. The external evidence was helpful in making clinical decisions for patient care.